Prenatal diagnosis of euploid increased nuchal translucency on fetal ultrasound (II): RASopathy disorders – Prenatal ultrasound findings and genotype–phenotype correlations - Chih-Ping Chen (Journal of Medical Ultrasound, 2023)
Prenatal diagnosis of euploid increased nuchal translucency (NT) remains a challenge to obstetricians and genetic counselors, although increased euploid NT at prenatal diagnosis can be associated with a favorable outcome. Prenatal diagnosis of euploid increased NT should include a differential diagnosis of pathogenetic copy number variants and RASopathy disorders (RDs) including Noonan syndrome. Therefore, chromosomal microarray analysis, whole-exome sequencing, RASopathy-disorder testing, and protein-tyrosine phosphatase nonreceptor type 11 gene testing may be necessary under such a circumstance. In this report, a comprehensive review of RDs with its prenatal ultrasound findings and genotype-phenotype correlations is presented.